Prevalence of pulp canal obliteration after traumatic dental injuries: a systematic review and meta-analysis - Mariana Gouvêa Latini ABREU; Thaís de Oliveira FERNANDES; Leonardo Santos ANTUNES; Lívia Azeredo Alves ANTUNES; Lucianne Cople Maia de FARIA (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract This systematic review aimed to answer the following question: What is the estimated prevalence of pulp canal obliteration in subtypes of traumatic dental injury (TDI) in deciduous and permanent teeth? The searches were conducted in PubMed, Embase, Scopus, Web of Science, LILACS, Grey Literature, and Google Scholar, and complemented by a manual search, until April 16th, 2023. Observational studies were selected based on population, exposure, and outcome (PEO) (P, deciduous or permanent teeth; E, TDI; O, pulp canal obliteration). Two reviewers (kappa 0.90) applied the eligibility criteria, extracted qualitative data, and assessed the methodological quality using the Newcastle-Ottawa tool. A meta-analysis was performed using MedCalc 17.2. Thirty-four articles were selected after screening. The methodological quality was moderate to high. The estimated prevalence of pulp canal obliteration was 27.6% (95%CI: 18.7-37.7) and 21.9% (95%CI:16.0-28.4), for permanent and deciduous teeth, respectively. Considering the TDI subtypes, the prevalence of pulp canal obliteration was higher in root fractures of the permanent teeth (78.6 %, 95%CI: 62.8-90.9) and lateral luxation injuries in deciduous teeth (29.4%, 95%CI:19.1-41.0). Our review of 34 articles of moderate and high methodological quality found that the prevalence of pulpal canal obliteration ranges from 21.9% to 27.6%. Pulp canal obliteration was most frequently detected following lateral luxation injuries of the deciduous teeth and root fractures of the permanent teeth (PROSPERO CRD42020179438).